global warming and health - Maria de Nazaré de Oliveira Fraga (Rev Rene)
Irony of ironies, those who first organizedinternationally to defend propositional wayenvironmental issues were treated as terroristsby the governments of various countries.Fortunately your ideal conquered fans whotoday are numerous, as numerous must be thefronts of struggle, given the complexity of these issues. In this regard, the passage ofindividual awareness for collective action andpolicy development by the various nation-states have long decades.